2016
DOI: 10.1002/14651858.cd011195.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheter (CVC) removal for patients of all ages with candidaemia

Abstract: Despite indications from observational studies in favour of early catheter removal, we found no eligible RCTs or quasi-RCTs to support these practices and therefore could draw no firm conclusions. At this stage, RCTs have provided no evidence to support the benefit of early or late catheter removal for survival or other important outcomes among patients with candidaemia; no evidence with regards to assessment of harm or benefit with prompt central venous catheter removal and subsequent re-insertion of new cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 114 publications
1
28
1
Order By: Relevance
“…We should be aware that all aforementioned studies, including the present one, were observational in design, possibly containing various biases and unmeasured potential confounders. No meta-analysis or randomized trials have yet been conducted to investigate the effect of early intervention in ICU patients with candidemia [17]. In the future, randomized studies targeting subgroups such as patients with septic shock due to candidemia could be considered, as several observational studies with positive results were derived from this population in the past [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…We should be aware that all aforementioned studies, including the present one, were observational in design, possibly containing various biases and unmeasured potential confounders. No meta-analysis or randomized trials have yet been conducted to investigate the effect of early intervention in ICU patients with candidemia [17]. In the future, randomized studies targeting subgroups such as patients with septic shock due to candidemia could be considered, as several observational studies with positive results were derived from this population in the past [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Raad and colleagues retrospectively analyzed 404 cancer patients with candidemia and CVCs and found that CVC removal within 72 h after onset of candidemia improved the response to antifungal therapy in patients with Candida-related CRBSI [199]. Similarly, findings from retrospective studies and a prospective cohort study in cancer patients with candidemia and systematic reviews indicate a decreased mortality in patients with CVC removal [204][205][206]. Therefore, prompt CVC removal is recommended in cancer patients with candidemia and yeast-related fungemias (e.g., Rhodotorula spp.)…”
Section: Catheter Removalmentioning
confidence: 99%
“…An individual patient‐level quantitative review of randomised trials for treatment of invasive candidiasis that assessed the impact of host‐, organism‐ and treatment‐related factors on mortality, identified removal of the CVC as a factor associated with improved survival and clinical cure . Recently, Janum et al reviewed 73 observational studies that reported on various clinically relevant outcomes following catheter removal or retention in paediatric and adult patients with candidemia . Forty of these observational studies reported a beneficial effect of catheter removal, 33 showed no clear difference, while none reported results in favour of catheter retention.…”
Section: Cvcs and Paediatric Candidemiamentioning
confidence: 99%
“…73 Recently, Janum et al reviewed 73 observational studies that reported on various clinically relevant outcomes following catheter removal or retention in paediatric and adult patients with candidemia. 74 Forty of these observational studies reported a beneficial effect of catheter removal, 33 showed no clear difference, while none reported results in favour of catheter retention. However, these studies were exceedingly heterogeneous with regard to population, pathogens and interventions, and suffered from confounding by indication and a high risk of bias.…”
Section: Vc S and Paed Iatri C C And Idemiamentioning
confidence: 99%